2007
DOI: 10.1108/09604520710735191
|View full text |Cite
|
Sign up to set email alerts
|

The current state of six sigma application in services

Abstract: 2002),"Critical success factors for the successful implementation of six sigma projects in organisations", The TQM Magazine, Vol. 14 Iss 2 pp. 92-99 http:// dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(145 citation statements)
references
References 36 publications
0
140
0
5
Order By: Relevance
“…The study also suggested that the problems of implementing the improvement tools and techniques are the same for both industries, therefore the solutions will be similar. Other studies have shown substantial benefits achieved by service sector organisations upon adoption of a variety of improvement tools and techniques including six sigma (Chakrabarty and Tan 2007) and lean manufacturing techniques (Amin and Karim 2013). For example, Esimai (2005) found that introducing lean six sigma into a US hospital environment gave the benefits of reduction in errors (a 55% reduction over a 5 month period), an estimated labour reduction of $1.32 million annually, improved employee morale, increased teamwork and an increase in patient satisfaction.…”
Section: Differences In Adoption and Resultsmentioning
confidence: 99%
“…The study also suggested that the problems of implementing the improvement tools and techniques are the same for both industries, therefore the solutions will be similar. Other studies have shown substantial benefits achieved by service sector organisations upon adoption of a variety of improvement tools and techniques including six sigma (Chakrabarty and Tan 2007) and lean manufacturing techniques (Amin and Karim 2013). For example, Esimai (2005) found that introducing lean six sigma into a US hospital environment gave the benefits of reduction in errors (a 55% reduction over a 5 month period), an estimated labour reduction of $1.32 million annually, improved employee morale, increased teamwork and an increase in patient satisfaction.…”
Section: Differences In Adoption and Resultsmentioning
confidence: 99%
“…There has been considerable research on the use of improvement initiatives (Sharma and Hoque 2002, Chen and Sawyers 1994, Chakrabarty and Tan 2007, Irfan et al 2012. While organisations in both developed and developing countries are likely to have used improvement initiatives to gain competitive advantage, it is commonly accepted that most improvement initiatives including Lean Management, 5S, TQM, BPR, Benchmarking and Balanced Scorecard were developed and first adopted by organisations in developed countries.…”
Section: Why Are Company Size and The Level Of National Development Imentioning
confidence: 99%
“…It is defined as a set of statistical tools adopted within the quality management to construct a framework for process improvement [9]. It is also as an operational philosophy of management which can be shared beneficially by customers, shareholders, employees and suppliers [10,11]. SS methodically analyses underlying data and identifies the root causes of problems as opposed to using subjective opinions.…”
Section: Six Sigma (Ss)mentioning
confidence: 99%